Mechanisms of GH action on the skeleton: role of SOCS2 - Dobie, Ross (The University of Edinburgh, 2015)
Determining the mechanisms by which growth hormone (GH) enhances bone growth and development has proven difficult. GH can act either systemically via the stimulation of liver insulin like growth factor (IGF)-1, or locally via activation of the GH receptor (GHR). Furthermore, the local actions of GH may be IGF-1 dependent (indirect) or independent (direct). Suppressor of cytokine signalling 2 (SOCS2) has been identified as an important regulator of GH signalling via the JAK/STAT pathway. The SOCS2 knockout (Socs2-/-) mouse is characterised by its overgrowth phenotype despite no elevation in systemic GH and IGF-1 levels. It therefore offers a valid and novel model to investigate the local effects of enhanced GH signalling on the skeleton. The work presented in this thesis investigates the Socs2-/- mouse model to better understand the actions of local GH on longitudinal bone growth and bone accrual. Ex vivo metatarsal organ cultures, osteoblast cultures, and in vivo approaches are used to unravel the mechanisms of GH action on the skeleton. This thesis also explores the potential of SOCS2 as primary mediator of inflammatory induced bone loss through the utilisation of the dextran sulphate sodium (DSS) model of colitis. Embryonic and postnatal ex vivo metatarsal organ cultures are used to study the mechanism of GH action on longitudinal bone growth. Specifically, the present work highlights that enhanced linear growth in the absence of SOCS2 is associated with an increase in the GH regulated proteins, IGF-2 and IGF binding protein 3 (IGFBP3), but not IGF-1. This indicates that IGF-1 may not be essential for mediating GH action on bone growth. Completion of an in depth analysis of the bone phenotype of juvenile and adult, male and female Socs2-/- mice reveals an anabolic phenotype consistent with increased GH signalling. Male Socs2-/- mice are shown to have a greater enhancement of cortical parameters compared to females, resulting in increased bone strength. Investigation of the mechanisms behind the enhanced bone accrual in Socs2-/- mice identifies SOCS2 as the primary SOCS protein regulating GH signalling in primary osteoblasts. The JAK/STAT pathway is confirmed as the key signalling pathway targeted by SOCS2. Despite this enhanced signalling there is little evidence presented in this thesis to suggest that GH actions on osteoblasts and ultimately bone mass are mediated through increased Igf1 expression. GH treatment is shown to be anabolic to bone of young juvenile Socs2-/- mice, but not WT mice. This increase in bone mass is associated with increase bone p-STAT5 signalling, but no increase in Igf1 levels indicating that GH may have IGF-1 independent effects in the Socs2-/- mouse model. GH treatment of young mice also reveals an age and sex specific effect of GH action where GH does not stimulate growth until approximately 3 weeks of age. From 3 weeks of age, WT female mice show increased growth in response to GH, but males do not. The increased growth is associated with increased p-STAT5 signalling and increased bone area. This thesis also confirms SOCS2 a critical mediator of bone loss associated with inflammation. The present results show that deteriorated trabecular bone health in colitic mice is associated with elevated Socs2 expression in bone. Furthermore, despite similar levels of gut inflammation observed in Socs2-/- mice with DSS induced colitis these mice are partly protected from poor bone health. The work described herein has used the Socs2-/- mouse model to strengthen our understanding of the actions of local GH on skeletal growth and development. It also provides compelling evidence for the importance of SOCS2 as a mediator of bone loss in cases of inflammatory bowel disease.
Keywords: GH; SOCS2; bone; growth